2011
DOI: 10.2807/ese.16.38.19973-en
|View full text |Cite
|
Sign up to set email alerts
|

Targeted screening and health education for Chagas disease tailored to at-risk migrants in Spain, 2007 to 2010

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 10 publications
3
68
1
7
Order By: Relevance
“…Our study found a high prevalence of Chagas disease. However, this could be overestimated because of the specific programs carried out by personnel at the Tropical Medicine Unit, which encouraged immigrants from endemic areas to undergo screening for T. cruzi infection 44 and so screening was probably performed in high-risk populations. We did not observe significant changes in prevalence with respect to the pre-consultation period, probably because of the prolonged asymptomatic phase of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a high prevalence of Chagas disease. However, this could be overestimated because of the specific programs carried out by personnel at the Tropical Medicine Unit, which encouraged immigrants from endemic areas to undergo screening for T. cruzi infection 44 and so screening was probably performed in high-risk populations. We did not observe significant changes in prevalence with respect to the pre-consultation period, probably because of the prolonged asymptomatic phase of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with positive or indeterminate results were recalled for collection of a further blood sample to detect anti-T. cruzi antibodies by conventional serum testing. This study was performed within a public health and surveillance program on Chagas' disease conducted by the Tropical Medicine Unit at the Ramón y Cajal Teaching Hospital (TMU-RCH) (26). To define the state of compromise and decide on further treatment, TMU-RCH conducted a thorough clinical assessment not described in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…This figure would be even greater if we consider the tablets needed to treat infected newborn children and adolescents, immunosuppressed patients, and non-Bolivian Chagas disease patients (the latter account for around 25% of the total number of infected patients [6][7][8][9][10][11] ). With this letter we would like to highlight that the shortage of benznidazole could become a public health problem even in non-endemic countries, as has occurred with other antiinfective drug shortages.…”
mentioning
confidence: 99%
“…These recommendations exclude patients with advanced chagasic cardiomyopathy. 4 To calculate the amount of benznidazole needed to treat adult Chagas disease patients in Spain different factors were considered (Table 1) Trypanosoma cruzi infection prevalence rates in adult migrants from Bolivia, calculated from studies performed in non-clinical settings (such as migrant associations), blooddonation centers, and maternity hospitals [6][7][8][9][10][11] : 15.5%. Around 5% of infected patients have severe disease, 20% have early visceral involvement, and 75% are asymptomatic.…”
mentioning
confidence: 99%